The EU Migrant Generation in Asia : Middle-Class Aspirations in Asian Global Cities - Hof, Helena (Global migration and social change., 2022)
Drawing on a comparative study with individuals who migrated to Singapore and Tokyo in 2010s, this book demonstrates how migration to Asian business centres has become an alternative to a middle-class life in Europe and how the perceived insecurities of life in the crisis-ridden EU result in these migrants' prolonged stay in Asia.